(untitled) (Research, Society and Development, 2022)
The training of qualified human resources for the professional exercise of teaching comprises one of the main commitments of the Teaching Area in Brazil, given that its postgraduate programs work in the development of research and didactic-pedagogical productions aimed at teaching and learning of specific contents, in order to promote dialogue between these contents and the pedagogical knowledge necessary for their teaching. In this way, in the curricular structure of master’s and doctoral courses in this Area, it is common to identify components aimed at teacher training. On this theme, a series of studies grouped under the terminology ’teaching knowledge’ have been used in the theoretical frameworks of articles, theses, and dissertations in the Area. Thus, in the current research, configured in a qualitative approach and inspired by a survey, the results of a survey carried out with postgraduate programs in the Teaching Area are presented, with the objective of investigating the presence of curricular and structural components (lines of research, areas of concentration, disciplines and research projects) specifically based on ’teaching knowledge’. In all, the websites of 174 programs that offer academic and professional master’s and doctoral courses were accessed. As a result, it was concluded that only 13 programs in the Area have a specific component on the topic of interest, characterizing an unexpectedly understated presence of the reference of teaching knowledge in the researched programs, although, contradictorily, there is a varied and wide offer of publications that use this reference as a theoretical support for the most varied studies on teacher training.